2020
DOI: 10.1002/jbmr.4009
|View full text |Cite
|
Sign up to set email alerts
|

Intervertebral Disc Degeneration Is Associated With Aberrant Endplate Remodeling and Reduced Small Molecule Transport

Abstract: The intervertebral disc is the largest avascular structure in the body, and cells within the disc rely on diffusive transport via vasculature located within the vertebral endplate to receive nutrients, eliminate waste products, and maintain disc health. However, the mechanisms by which small molecule transport into the disc occurs in vivo and how these parameters change with disc degeneration remain understudied. Here, we utilize an in vivo rabbit puncture disc degeneration model to study these interactions an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(55 citation statements)
references
References 59 publications
1
54
0
Order By: Relevance
“…Recent studies support the hypothesis of a global approach to back pain pathologies, since changes in the vertebral bone, especially in the endplates, influence the transport of nutrients to the disc and its eventual degeneration (35). The appropriate crosstalk between the IVD and the subchondral bone is a key feature of the homeostasis of the intervertebral joint functional unit (IVD, the upper and lower vertebrae, and the facet joints) (17).…”
Section: Discussionmentioning
confidence: 93%
“…Recent studies support the hypothesis of a global approach to back pain pathologies, since changes in the vertebral bone, especially in the endplates, influence the transport of nutrients to the disc and its eventual degeneration (35). The appropriate crosstalk between the IVD and the subchondral bone is a key feature of the homeostasis of the intervertebral joint functional unit (IVD, the upper and lower vertebrae, and the facet joints) (17).…”
Section: Discussionmentioning
confidence: 93%
“…The Masuda scoring system for disc degeneration included categories for characterizing changes to the AF and NP, but did not include scoring of the EP to assess cartilage and bony EP remodeling, or scoring for cellular changes occurring with regeneration which provides information on the biological action of regenerative strategies. Scoring of these features was therefore included in the proposed scoring system, modified from scoring systems utilized by Chujo et al 18 and Ashinsky et al 20 Because the use of decalcified, paraffin processed sections is recommended for scoring, the endplate features included in the scoring system are focused solely on morphologic changes to this region. Researchers interested in studying alterations in calcification of this region would need to employ alternative methods, such as microcomputed tomography or cryo‐ or plastic sectioning to quantify or visualize endplate calcification.…”
Section: Discussionmentioning
confidence: 99%
“…Degenerative intervertebral disc is a kind of hypoxia, nutrient deficiency, slightly acidic, high osmotic pressure, high mechanical stress of the poor internal environment. Puluqiao et al found that the apoptosis of CESCs increased and the expression of apoptosis‐related proteins BNIP3, Bax and Bak upregulated under the condition of hypoxia and nutrient deficiency 20,21 . He et al found that low nutrient environment can induce high expression of BNIP3 protein in CESCs and induce apoptosis of CESCs through BNIP3 related signal pathway 22 .…”
Section: Discussionmentioning
confidence: 99%